If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -1(-2) = 68 Multiply -1 * -2 c + 2 = 68 Reorder the terms: 2 + c = 68 Solving 2 + c = 68 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + c = 68 + -2 Combine like terms: 2 + -2 = 0 0 + c = 68 + -2 c = 68 + -2 Combine like terms: 68 + -2 = 66 c = 66 Simplifying c = 66
| 3y+4=-20 | | 56=4y | | 50=(x+10)x | | [(5*6-4)-20]= | | 2a+10=26 | | c+-52=68 | | x-9.51=2.4 | | -2b+8=-8 | | 241=5(5-7x)+8x | | 3c+5=-13 | | -5+(8-14)-(-4-9)= | | 17=3(p-4)+8 | | 10n-15=85 | | -2b+(-3)=7 | | -5.6+-15= | | 4m-13=15 | | 4.5x+13.5x=2.5-x+3 | | 3b+6(-6)=-12 | | -5(8-14)-(-4-9)= | | 4x-3x=2x+5 | | -2b+1=5 | | 2(3x-4)=-(4x+6) | | 3a+(-2)=-5 | | -27+17+(-1)= | | 2a+3c= | | 2x+(-4)=14 | | 4.5x+13.5=2.5-x+3 | | -3z+8=35 | | 25x+63x-x=40 | | -2y+5=25 | | m+7m-7m-2= | | 126+43h=53.5h |